Integration of mental and psychomotor training in vocational rehabilitation for persons with mental illness improves employment - Jan , Knapen (International Journal of Psychosocial Rehabilitation, 2016)
Common mental health problems, such as depression, burnout, personality disorders, anxiety- and somatoform disorders are often associated with unemployment. Employment is for many people with a mental vulnerability not only a source of financial income, but employment also determines their social status and inclusion, identity and self-image.In order to increase the employment rate of people with a mental vulnerability a centre for vocational rehabilitation in Belgium (AZERTIE) developed the I Care program.The I Care program, a combination of psychomotor and mental training, resulted in a employment over than 50% of people with a mental vulnerability. After at least one year employment 90% was still at work. When we compare the employment rate (over than 50%) with the rate of the period before the start-up of the I Care program (10%), we can conclude that the I Care program increased the employment of this vulnerable group five-fold.